The association between chronological age and maturity status on lower body clinical measurements and asymmetries in elite youth tennis players - Lopez-Valenciano, A.; Ayala, F.; De Ste Croix, M. B. A.; Barbado, D.; Moreno-Perez, V.; Sanz-Rivas, D.; Fernandez-Fernandez, J. (Sports Health: A Multidisciplinary Approach, 2023)
Background: Tennis is one of the most popular sports among youths. At elite levels, a notable increase in injury incidence and a temporary decline in performance may occur when children progress through puberty. However, limited research has explored maturity-associated variations in clinical measurements suggested as predictors of injury and tennis performance in elite youth players. Therefore, the main purpose of this study was to analyze the association between chronological age and maturity status on several measures of neuromuscular capability and physical performance as well as bilateral (interlimb) asymmetries in elite youth tennis players.